TINGKAT KESUKAAN BAKSO IKAN BERBAHAN BAKU UTAMA DAGING IKAN AIR TAWAR : ABSTRACT, PENDAHULUAN, METODE PENELITIAN, HASIL DAN PEMBAHASAN, KESIMPULAN, UCAPAN TERIMA KASIH DAN DAFTAR PUSTAKA - -, Junianto; Nisrina Khoirunnisa; Dhafin Fadhlur Rahman; M. Fariduddin Muslim (Program Studi Teknologi Hasil Perikanan|Fakultas Pertanian|Universitas PGRI Banyuwangi, 2024)
Freshwater fish have great potential to be used as raw material for fish balls. Types of freshwater fish that can be processed into fish balls, such as catfish, tilapia and catfish. This research aims to determine the right type of freshwater fish meat as the main raw material in making fish balls to obtain the most preferred product. The research method used was experimental with 3 treatments of freshwater fish meat, namely African catfish, catfish and tilapia. The meatball products obtained were observed for the level of preference for appearance, aroma, texture and taste. The assessment was carried out by 15 semi-trained panelists using Bayes tests. The data obtained were analyzed using the Friedman test, pairwise comparisons and the Bayes method. The results showed that the level of preference for the aroma, texture and taste of fish meatballs was influenced by the type of freshwater fish meat used, while the appearance level was not affected. The most popular fish balls are fish balls made from African catfish meat.